1998
DOI: 10.1002/(sici)1097-4652(199812)177:4<593::aid-jcp10>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the clusterin gene by Ha-ras and c-myc oncogenes and during apoptosis

Abstract: Clusterin (ApoJ) is an extracellular glycoprotein expressed during processes of tissue differentiation and regression that involve programmed cell death (apoptosis). Increased clusterin expression has also been found in tumors, however, the mechanism underlying this induction is not known. Apoptotic processes in tumors could be responsible for clusterin gene activation. Alternatively, oncogenic mutations could modulate signal transduction, thereby inducing the gene. We examined the response of the rat clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
(21 reference statements)
0
11
0
4
Order By: Relevance
“…values are presented. HC11 (C) vs. HC11 ras (C): p = 0.037; HC11 (C) vs. HC11 ras (F): p = 0.037; HC11 ras (C) vs. HC11 ras (F): p = 0.037. could downregulate the transcription of some genes, such as LUCA15, a tumor suppressor gene [24] and clusterin, an extracellular glycoprotein involved in apoptosis [25] in Rat 1 fibroblasts, as well as Wnt5a and Wnt7a, genes involved in tumor growth and cell adhesion regulation, in a normal spontaneously immortalized human mammary epithelial cell line, MCF-10A [26]. In a previous work, we have reported that NIH3T3 ras transformed fibroblasts displayed lower glucocorticoid receptor (GR) citoplasmatic levels [27] in part caused by a reduced transcription of the GR gene [28], which seemed to be associated with H-ras cellular transformation.…”
Section: Discussionmentioning
confidence: 99%
“…values are presented. HC11 (C) vs. HC11 ras (C): p = 0.037; HC11 (C) vs. HC11 ras (F): p = 0.037; HC11 ras (C) vs. HC11 ras (F): p = 0.037. could downregulate the transcription of some genes, such as LUCA15, a tumor suppressor gene [24] and clusterin, an extracellular glycoprotein involved in apoptosis [25] in Rat 1 fibroblasts, as well as Wnt5a and Wnt7a, genes involved in tumor growth and cell adhesion regulation, in a normal spontaneously immortalized human mammary epithelial cell line, MCF-10A [26]. In a previous work, we have reported that NIH3T3 ras transformed fibroblasts displayed lower glucocorticoid receptor (GR) citoplasmatic levels [27] in part caused by a reduced transcription of the GR gene [28], which seemed to be associated with H-ras cellular transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Four permanent mammalian tumor cell lines were applied to determine the cytotoxic effect caused by MTN: murine leukemic lymphoblasts L5178y (ATCC CRL 1722), rat adrenal pheochromocytoma cells PC-12 (ATCC CRL 1721), human cervix HeLa S3 cells (ATCC CCL 2.2) and the rat embryonal fibroblast cells Rat1 (Klock et al, 1998). The tumor cells were grown as described previously (Müller et al, 1977;Bartl et al, 2001) with the modification that RPMI 1640 medium, enriched with 10% fetal calf serum was used.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Clusterin is a conserved glycoprotein, also known as apolipoprotein J, whose expression is increased in many cell types in response to stress. Clusterin has been reported to have chaperonin-like activity (22) and anti-inflammatory activity (32), and it is expressed during tissue differentiation and remodeling involving apoptosis (26,29).…”
Section: Vol 75 2001mentioning
confidence: 99%